Research progress on anti-ovarian cancer mechanism of miRNA regulating tumor microenvironment - Cui, MingHua; Liu, YueHui; Cheng, Li; Li, Tao; Deng, YongZhi; Liu, Da (Frontiers in Immunology, 2022)
Ovarian cancer is the most deadly malignancy among women, but its complex pathogenesis is unknown. Most patients with ovarian cancer have a poor prognosis due to high recurrence rates and chemotherapy resistance as well as the lack of effective early diagnostic methods. The tumor microenvironment mainly includes extracellular matrix, CAFs, tumor angiogenesis and immune-associated cells. The interaction between tumor cells and TME plays a key role in tumorigenesis, progression, metastasis and treatment, affecting tumor progression. Therefore, it is significant to find new tumor biomarkers and therapeutic targets. MicroRNAs are non-coding RNAs that post-transcriptionally regulate the expression of target genes and affect a variety of biological processes. Studies have shown that miRNAs regulate tumor development by affecting TME. In this review, we summarize the mechanisms by which miRNAs affect ovarian cancer by regulating TME and highlight the key role of miRNAs in TME, which provides new targets and theoretical basis for ovarian cancer treatment.